1997
DOI: 10.4102/lit.v18i3.546
|View full text |Cite
|
Sign up to set email alerts
|

Tales of transition

Abstract: Tales of transitionIn this article the rationale o f this special issue is pro vid ed a n d the different contributions are introduced. The assumption is that there are strong similarities between the recent political a n d social transitions in South A frica and G erm any and the reactions, both emotional a n d literary, o f the people involved. Broadly, the transitions are described as a m ovement fro m external (or violent) to internal (or ideological) social control, though this must be m odified by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…7 COVID-19 and the resulting lockdowns had an impact on divorce and marriages worldwide, applications for marriage licenses declined in countries that require them, couples postponed marriages, spouses that were unhappy staying married were forced to stay together, and there were various barriers to obtaining a divorce such as earning less or no income due to lockdown and court delays or closed courts. 8 that there has been an increase in divorce and applications for divorce since lockdown. 9 Daniel 10 indicates that there are large backlogs at the courts and that in Limpopo province alone, there were 11 788 divorces outstanding at the end of 2020.…”
Section: Faculty Of Law University Of Johannesburgmentioning
confidence: 99%
See 4 more Smart Citations
“…7 COVID-19 and the resulting lockdowns had an impact on divorce and marriages worldwide, applications for marriage licenses declined in countries that require them, couples postponed marriages, spouses that were unhappy staying married were forced to stay together, and there were various barriers to obtaining a divorce such as earning less or no income due to lockdown and court delays or closed courts. 8 that there has been an increase in divorce and applications for divorce since lockdown. 9 Daniel 10 indicates that there are large backlogs at the courts and that in Limpopo province alone, there were 11 788 divorces outstanding at the end of 2020.…”
Section: Faculty Of Law University Of Johannesburgmentioning
confidence: 99%
“…The researchers found that 454 children under 5 years of age were killed in 2009. 8 Only eight out of a total of 241 neonates (referring to a child that is 28 days old or younger) were more than six days old when they died. 9 These findings were underestimates because of the difficulty in distinguishing between infanticide (the killing of an infant within the first year of life) and other causes of death during infancy.…”
Section: Covid-19 and Its Impact On Children In Sa With A Specific Lo...mentioning
confidence: 99%
See 3 more Smart Citations